2014
DOI: 10.1530/eje-14-0195
|View full text |Cite
|
Sign up to set email alerts
|

Association of HDL-C and apolipoprotein A-I with the risk of type 2 diabetes in subjects with impaired fasting glucose

Abstract: Objectives: HDLs have many diverse functions. The goal of this study was to determine the association of HDL cholesterol (HDL-C) and apolipoprotein A-I (apoA-I) with the development of type 2 diabetes (T2D). In particular, this study determined the association between the ratio of HDL-C to apoA-I (HA) and incident T2D. Design and methods: A total of 27 988 subjects with impaired fasting glucose (IFG) (18 266 men and 9722 women) aged 21-91 years (mean age 40.7 years) were followed for a mean duration of 2.81 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 28 publications
1
28
0
3
Order By: Relevance
“…However, this association has not been found to be consistent in previous studies [22][23][24][25] although previous research suggested that ApoA1 affects glucose metabolism via multiple mechanisms, including enhanced insulin secretion [26], increased insulin-independent glucose uptake in muscle and adipose tissues [27,28], improved insulin sensitivity [29], and reversed adipocyte dysfunction [30] and restored adiponectin expression and insulin sensitivity [31] with ApoA1 mimetic peptide. Furthermore, genetic studies suggested that genetic variation in ABCA1 has been associated with the increased risk of T2DM [32], and one study suggested that loss-of-function mutations in ABCA1 were associated with impaired b-cell function, but not with the development of T2DM [33].…”
Section: Discussionmentioning
confidence: 49%
“…However, this association has not been found to be consistent in previous studies [22][23][24][25] although previous research suggested that ApoA1 affects glucose metabolism via multiple mechanisms, including enhanced insulin secretion [26], increased insulin-independent glucose uptake in muscle and adipose tissues [27,28], improved insulin sensitivity [29], and reversed adipocyte dysfunction [30] and restored adiponectin expression and insulin sensitivity [31] with ApoA1 mimetic peptide. Furthermore, genetic studies suggested that genetic variation in ABCA1 has been associated with the increased risk of T2DM [32], and one study suggested that loss-of-function mutations in ABCA1 were associated with impaired b-cell function, but not with the development of T2DM [33].…”
Section: Discussionmentioning
confidence: 49%
“…In the case of low‐density lipoprotein (LDL), concomitant measure of its major lipoprotein, namely, apolipoprotein B 100 (apoB), has clarified the epidemiological risk related to LDLs of different sizes and densities, and it would therefore appear relevant to also adjust HDL‐C to its major apolipoprotein, namely, apolipoprotein A‐I (apoA‐I). The easiest way to combine these 2 measures is to calculate their ratio [HDL‐C/apoA‐I], bearing in mind that unlike the single molecular ratio of apoB 100 vis‐à‐vis LDL, discoidal or spherical mature HDLs carry 2 or 4 apoA‐Is per particle . Such a ratio allows not only to estimate an average size for HDLs but also to derive useful indices of HDL number, cholesterol load, and density.…”
Section: Introductionmentioning
confidence: 99%
“…However, in replacement therapy for hypothyroidism, the weight loss is very modest and due more to water deficit than to changes in body fat. Moreover, treatment of obese euthyroid patients with levothyroxine does not induce weight changes (1,2,3,4,5). …”
Section: Introductionmentioning
confidence: 99%
“…In obese subjects, slight increases have been observed in thyrotropin, or thyroid-stimulating hormone (TSH), but these are far from being the cause of overweight and could rather be a consequence of it (1,2,3,4,5). Although the origin of this increase in TSH in obese subjects is not fully understood and may be multifactorial, rather than being an indicator of subclinical hypothyroidism or of thyroid hormone resistance, it is currently considered to be an adaptive change, an attempt to increase basal metabolism in order to avoid further weight gain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation